The combination of loss of glyoxalase1 and obesity results in hyperglycemia - Lodd, Elisabeth; Wiggenhauser, Lucas; Morgenstern, Jakob; Fleming, Thomas; Poschet, Gernot; Büttner, Michael; Tabler, Christoph Tobias; Wohlfart, David Philipp; Nawroth, Peter Paul; Kroll, Jens (JCI insight, 2019)
The increased formation of methylglyoxal (MG) under hyperglycemia is associated with the development of microvascular complications in patients with diabetes mellitus; however, the effects of elevated MG levels in vivo are poorly understood. In zebrafish, a transient knockdown of glyoxalase 1, the main MG detoxifying system, led to the elevation of endogenous MG levels and blood vessel alterations. To evaluate effects of a permanent knockout of glyoxalase 1 in vivo, glo1–/– zebrafish mutants were generated using CRISPR/Cas9. In addition, a diet-induced–obesity zebrafish model was used to analyze glo1–/– zebrafish under high nutrient intake. Glo1–/– zebrafish survived until adulthood without growth deficit and showed increased tissue MG concentrations. Impaired glucose tolerance developed in adult glo1–/– zebrafish and was indicated by increased postprandial blood glucose levels and postprandial S6 kinase activation. Challenged by an overfeeding period, fasting blood glucose levels in glo1–/– zebrafish were increased which translated into retinal blood vessel alterations. Thus, the data have identified a defective MG detoxification as a metabolic prerequisite and glyoxalase 1 alterations as a genetic susceptibility to the development of type 2 diabetes mellitus under high nutrition intake.